Lasing in inert gases with pumping by the electron beam of an accelerator with a plasma cathode; Soviet Physics. Doklady; Vol. 31 - Vintizenko L. G.; Gushenets V. I.; Koval N. N.; Koval B. A.; Mesyats G. A. Gennady Andreyevich; Skakun V. S.; Tarasenko V. F.; Fedenev A. V.; Schanin P. M. (1986, 1986)
В фонде НТБ ТПУ отсутствует